Mitochondrial dysfunction of induced pluripotent stem cells-based neurodegenerative disease modeling and therapeutic strategy - Luo, Hong-Mei; Xu, Jia; Huang, Dan-Xia; Chen, Yun-Qiang; Liu, Yi-Zhou; Li, Ya-Jie; Chen, Hong (Frontiers in Cell and Developmental Biology, 2022)
Neurodegenerative diseases (NDDs) are disorders in which neurons are lost owing to various factors, resulting in a series of dysfunctions. Their rising prevalence and irreversibility have brought physical pain to patients and economic pressure to both individuals and society. However, the pathogenesis of NDDs has not yet been fully elucidated, hampering the use of precise medication. Induced pluripotent stem cell (IPSC) modeling provides a new method for drug discovery, and exploring the early pathological mechanisms including mitochondrial dysfunction, which is not only an early but a prominent pathological feature of NDDs. In this review, we summarize the iPSC modeling approach of Alzheimer’s disease, Parkinson’s disease, and Amyotrophic lateral sclerosis, as well as outline typical mitochondrial dysfunction and recapitulate corresponding therapeutic strategies.